2022
DOI: 10.48550/arxiv.2204.12774
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Matter & Mind Matter

Abstract: As a result of a hundred million years of evolution, living animals have adapted extremely well to their ecological niche. Such adaptation implies species-specific interactions with their immediate environment by processing sensory cues and responding with appropriate behavior. Understanding how living creatures perform pattern recognition and cognitive tasks is of particular importance for computing architectures: by studying these information pathways refined over eons of evolution, researchers may be able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 173 publications
(292 reference statements)
0
1
0
Order By: Relevance
“…to investigate learning in cultures [169,173]. Long-term stimulation is particularly interesting because it has been suggested that the underlying structure should reflect the emergent dynamics, and, driven by long-term adaptation mechanisms, vice versa [32,159,179]. In particular, near-critical dynamics would go hand-in-hand with an underlying network structure that is also poised in-between lattice-like order and randomness.…”
Section: Next Stepsmentioning
confidence: 99%
“…to investigate learning in cultures [169,173]. Long-term stimulation is particularly interesting because it has been suggested that the underlying structure should reflect the emergent dynamics, and, driven by long-term adaptation mechanisms, vice versa [32,159,179]. In particular, near-critical dynamics would go hand-in-hand with an underlying network structure that is also poised in-between lattice-like order and randomness.…”
Section: Next Stepsmentioning
confidence: 99%